2013
DOI: 10.1016/j.kjms.2013.05.006
|View full text |Cite
|
Sign up to set email alerts
|

The impact of an interprofessional problem‐based learning curriculum of clinical ethics on medical and nursing students' attitudes and ability of interprofessional collaboration: A pilot study

Abstract: Clinical ethic situations in modern multiprofessional healthcare systems may involve different healthcare professions who work together for patient care. The undergraduate interprofessional education of clinical ethics would help to incubate healthcare students' ability of interprofessional collaboration in solving ethical problems. However, the impact from an interprofessional educational model on student's attitudes and confidence of interprofessional collaboration should be carefully evaluated during the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 22 publications
1
45
0
2
Order By: Relevance
“…It indicated that medical students were accustomed to work in teams attributable to the medical program implemented problem based learning (PBL) since the first year, while the other disciplines applied lecture-based learning in large classroom. This evidence supported previous studies that the ability to cooperate formed through a continual process and PBL had developed students' ability to resolve conflicts within the team, developing a good group process, and better to adapt on different professional behavior in an interprofessional team [16].…”
Section: Student Writen Commentssupporting
confidence: 89%
“…It indicated that medical students were accustomed to work in teams attributable to the medical program implemented problem based learning (PBL) since the first year, while the other disciplines applied lecture-based learning in large classroom. This evidence supported previous studies that the ability to cooperate formed through a continual process and PBL had developed students' ability to resolve conflicts within the team, developing a good group process, and better to adapt on different professional behavior in an interprofessional team [16].…”
Section: Student Writen Commentssupporting
confidence: 89%
“…Students reported self-perceived improvement in IPC and the increased ability to adapt different communication styles in future practices (2,15,51,52,55,59,65,69,75,77,78,80,81,83,86,101,106,115,116).…”
Section: Discussionmentioning
confidence: 99%
“…While the findings reported by Lin and colleagues [18] suggest that a problem-based interprofessional learning curriculum can positively impact nursing and medical students' attitudes toward and confidence in interprofessional collaboration, several limitations are noteworthy besides the small sample size. First, the authors fail to provide robust details of the PBL curriculum intervention, which limits the replication of findings.…”
Section: Lin Et Al's Study Of Interprofessional Clinical Ethics Educmentioning
confidence: 91%
“…In 2013, Lin and colleagues piloted an interprofessional problembased learning (PBL) curriculum in clinical ethics education to evaluate students' attitudes and confidence when performing collaborative teamwork [18]. Thirty-six nursing and medical students in Taiwan were recruited and randomly divided into three groups (nursing group, medical group, and cross-disciplinary group).…”
Section: Lin Et Al's Study Of Interprofessional Clinical Ethics Educmentioning
confidence: 99%